2005
DOI: 10.4315/0362-028x-68.9.1874
|View full text |Cite
|
Sign up to set email alerts
|

Educational Intervention Enhances Consumers' Readiness To Adopt Food Thermometer Use When Cooking Small Cuts of Meat: An Application of the Transtheoretical Model

Abstract: An intervention to promote use of food thermometers when cooking small cuts of meat was conducted using the Transtheoretical Model. Objectives were to (i) increase use of food thermometers by home food preparers, (ii) improve consumers' attitudes regarding use of a food thermometer, and (iii) examine relationships between stages of change and decisional balance, self-efficacy, and processes of change. A randomly selected group of residents of Washington and Idaho (n = 2,500) were invited to participate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 11 publications
2
45
0
Order By: Relevance
“…All the studies identified through electronic database searching were reported in published journal articles. Partial results from two studies (Takeuchi et al, 2005a;Takeuchi et al, 2005b) were also reported in a section of another somewhat larger paper examining food thermometer usage (McCurdy et al, 2006). For the purposes of this paper the studies were only discussed as a part of the original papers as they contained greater detail.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the studies identified through electronic database searching were reported in published journal articles. Partial results from two studies (Takeuchi et al, 2005a;Takeuchi et al, 2005b) were also reported in a section of another somewhat larger paper examining food thermometer usage (McCurdy et al, 2006). For the purposes of this paper the studies were only discussed as a part of the original papers as they contained greater detail.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The Takeuchi studies (Takeuchi et al, 2005a;Takeuchi et al, 2005b) were the only studies that reported results in terms of Social Cognition Models. In both studies, results generally found that interventions were successful in moving some participants through to the next stages of the TTM (See Table 2 for full results).…”
Section: Social Cognition Modelsmentioning
confidence: 99%
See 3 more Smart Citations